Impact of human activities on the Marchica lagoon ecosystem in northeast Morocco - Hlal Mohammed; El Monhim Bilal; Bouymajjan Mohamed; Sbai Abdelkader; Benrbia Khadija; Cwick Gary; El Harradji Abderrahmane; Benata Mohamed; Saidi Abdelouahid (E3S Web of Conferences)
This study aims to analyze and assess the human-induced pressures on the Marchica lagoon ecosystem in north-eastern Morocco, a designated Site of Biological and Ecological Interest (SBEI) known for its rich biodiversity. Employing a multifaceted approach, the research will: examine existing scientific literature on the lagoon's biodiversity and documented human activities, utilize spatial data (e.g., land use maps, pollution levels) to assess the spatial distribution of human activities and potential impacts, and potentially conduct field observations to gather data on the current state of the lagoon. However, human activities have progressively exerted ever-increasing pressure on this fragile ecosystem more than 70% of the pressure comes from urban and agricultural activities. This comprehensive analysis aims to identify and quantify human-induced pressures on the lagoon's health and biodiversity, ultimately highlighting the importance of SBEI preservation and informing future management strategies for the lagoon's long-term sustainability.